(untitled) - Erfina Erfina; Kusrini Semarwati Kadar; Suni Hariati; Nurmaulid Nurmaulid (University of Ostrava, 2021)
Aim: The aim of this study was to evaluate the utilization of healthcare services for pregnant women during the COVID-19 pandemic in South Sulawesi, Indonesia. Design: An analytical cross-sectional study. Methods: A group of 226 pregnant women completed the study questionnaire. The questionnaire was developed based on the basic health research questionnaire from the Ministry of Health, Indonesia, and the Navigating Pregnancy during the COVID-19 Pandemic article from UNICEF. Results: Of the 226 pregnant women, 122 (54%) had poor knowledge related to COVID-19 and negative attitudes regarding health protocols for COVID-19 (79.6%). Most (n = 189; 83.6%) experienced anxiety; however, this did not affect their intention to use healthcare services. Utilization of antenatal care services during the pandemic was associated with antenatal care visiting behavior (p = 0.000) and access to healthcare services (p = 0.000). The most significant predictor of utilization of antenatal care services during the pandemic was antenatal care visiting behavior (p = 0.002; OR = 5.904). Conclusion: These findings provide important information on maternal healthcare provision during the pandemic in Indonesia.